Case Report: A rare case of breast leiomyoma with literature review - Feng, Xiao; Zeng, Shue (Frontiers in Oncology, 2026)
Breast leiomyoma is a rare benign mesenchymal tumor that typically manifests as a solitary, slow-growing mass. This article presents a case of a 58-year-old female with a history of follicular lymphoma confirmed by pathological examination of resected lymph nodes in November 2019. Follow-up positron emission tomography/computed tomography (PET-CT) revealed a breast soft-tissue mass initially classified as likely benign. Subsequent chest computed tomography (CT) in May 2024 demonstrated enlargement of the lesion, raising suspicion of lymphomatous infiltration. The mammogram shows an irregular mass shadow with shallow lobulation and scattered punctate and coarse calcification shadows. It is classified as BI-RADS 4b. Multimodal ultrasound evaluation (including grayscale ultrasound, color doppler, shear-wave elastography, strain elastography, and contrast-enhanced ultrasound) identified a solid breast mass categorized as BI-RADS 4b. Ultrasound-guided core needle biopsy revealed adenosis with focal fibroadenomatoid changes. Definitive diagnosis was achieved through surgical excision, with histopathology demonstrating fascicular arrangements of spindle-shaped smooth muscle cells on hematoxylin-eosin staining, corroborated by immunohistochemical confirmation (SMA+/desmin+). Postoperative surveillance at 6 months showed no recurrence. A search was conducted in the PubMed database using “breast leiomyoma” as the keyword, with the publication date limited to January 1, 2015, to May 3, 2025. A total of 192 articles were retrieved. After applying rigorous selection criteria, 11 case reports that met the criteria were finally included for systematic review, involving a total of 12 cases of pathologically confirmed breast leiomyoma (one report contained 2 cases). Notably, only one study comprehensively characterized the contrast-enhanced ultrasound features, and no elastography examination was performed in any of the cases. This report presents a case of breast leiomyoma in a patient with a history of lymphoma. The imaging features were highly suggestive of malignancy, yet histopathological examination confirmed a benign lesion. This study aims to analyze the clinical and preoperative imaging characteristics of this case. Combined with a comprehensive literature review, it thoroughly explores the diagnostic imaging manifestations of breast leiomyoma, providing a reference for clinical differential diagnosis.